STEM ANATOMY and DEVELOPMENT of SUCCESSIVE CAMBIA IN THE NEOTROPICAL LIANA SECURIDACA RIVINIFOLIA (POLYGALACEAE) - Rajput, Kishore Shankersinh [UNESP]; Fiamengui, Marina B. [UNESP]; Marcati, Carmen Regina [UNESP] (Int Assoc Wood Anatomists, 2012)
The pattern of secondary growth and structure of secondary xylem was studied in the stem of the Neotropical liana Securidaca rivinifolia A. St.-Hil. (Polygalaceae). Increase in thickness of the stem was achieved by formation of successive cambia, from which initially two or three successive rings formed complete oval to circular cambia. Thereafter, the successive cambia were always crescent-shaped and never formed a complete cylinder, resulting in dumbbell-shaped cross-sectional outlines of the stems. The first successive cambium originated in the pericyclic parenchyma located outside the crushed protophloem. Prior to the development of cambium, pericyclic parenchyma formed a meristematic band of radially arranged cells. From this band, cells located in the middle of the band became the new ring of cambium. Cells on the inner face of the xylem produced by newly formed cambium differentiated into conjunctive tissue. The first elements to be differentiated from the newly developed cambium were always xylem fibres but differentiation of vessels was also observed occasionally. The xylem was diffuse porous with relatively distinct growth rings and composed of mostly solitary vessels with simple perforation plates, fibres with bordered pits, paratracheal axial parenchyma, and exclusively uniseriate rays.
Keywords: Cambial variant; Polygalaceae; secondary phloem; secondary xylem; Securidaca; successive cambia